Perceptions of Canadian Indigenous teachers and students on movement integration in the classroom. Issue 1 (14th August 2021) - Kerpan, Serene; Humbert, M. Louise; Abonyi, Sylvia
Abstract: The focus of this article is understanding the perceptions that Canadian Indigenous teachers and students have on a novel physical activity teaching method that is utilised in the classroom. We explore the role that physical activity plays in the healthy growth and development of children, with special attention to Indigenous children. Through participatory action research and qualitative methods, Indigenous teachers and students share their thoughts on physical activity in the classroom and the barriers and facilitators that exist to implementing classroom physical activity. This work is discussed in the context of the recent Truth and Reconciliation Commission of Canada and provides the reader with tangible suggestions for movement integration in the classroom.